Burden of Pulmonary Tuberculosis and Its Radiological Pattern, in Asymptomatic Young Males in Karachi, Pakistan - Zaidi, Huma; Shah, Haider Hussain; Nasrullah, Farhan; Ihsan, Hussain Rashid; Khan, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To estimate the burden of pulmonary tuberculosis among asymptomatic young male applicants in a government organization in Pakistan and to find out the pattern of disease on chest x-ray and high-resolution CT chest. Study Design: Prospective longitudinal study. Place and Duration of Study: Pakistan Air Force (PAF) Faisal Base Hospital Karachi, Pakistan, from Dec 2017 to Feb 2019. Methodology: An active search for detecting pulmonary tuberculosis was conducted in 1819 asymptomatic young male adults between 18 and 30 years who had applied for employment in a government organization with a pay scale ranging from 2 to 14 grade. Screening chest x-ray (CXR) was done as a part of their medical examination. High-resolution CT chest, sputum smear bacilloscopic and GeneXpert mycobacterium tuberculosis/resistance to Rifampicin assay tests were done in cases in which chest x-ray was suggestive of pulmonary tuberculosis. Results: Chest x-Ray and high-resolution CT of five out of 1819 male applicants were suggestive of pulmonary tuberculosis. Three cases (0.16%) were confirmed as positive on lab tests. Radiographic and High-resolution CT patterns showed upper lobe lesions, consistent with the radiological appearance of the immuno-competent host disease. Conclusion: The considerable presence of pulmonary tuberculosis was detected among asymptomatic young adults of this region; therefore, formulating a strategy to actively detect and treat analogous populations with high susceptibility to Pulmonary tuberculosis could help reduce this endemic disease.